574 Enhancing cooperation of medical and social services to improve aid to victims of violence in Zambia. (1st September 2016) - Mtonga, Robert; Valenti, Maria; Schober, Michael; Valenti, Maria; Hametner, Stephanie
Abstract : Background: In Zambia, gender-based violence (GBV) is on the rise, with one in five women having experienced sexual violence, and domestic violence frequently reported. Zambia has been working to tackle this. At the 66th World Health Assembly Zambia was one of seven countries that introduced a resolution on violence against women and girls and has also introduced national policies on GBV. Methods: A prospective study that was premised on pilot phase that compared a period prior to an intervention with another period following an intervention to study challenges to addressing GBV in Zambia include effective implementation, limited financial and human resources, and lack of public awareness. Health professionals from Zambia and Austria collaborated to design a research and education project to address these issues and improve care outcomes for victims of interpersonal violence (IPEV). It was designed to build on existing health and social services infrastructures, improve networking among medical and social services, and below-cost. The intervention included training for medical and social service personnel and distribution at key locations of information on services available to IPEV victims. Results: Capitalising on existing resources, linking local services, and developing a low-cost intervention kept costs down in resource poor Zambia, where the annual government per capita health expenditure is US32 or about 11% of the annual national budget. Sustainability was encouraged by engaging local partners. Results: victims of IPEV had improved understanding of available social services; improved networking among partner organisations; new descriptive data about victims, and; for medical participants, improved cross-cultural understanding. Conclusions: Low-cost interventions may improve care for victims of violence in resource-poor settings. Improved cooperation among social service and medical providers may benefit victims of IPEV and also agencies through strengthened relationships and information flow. North–South cooperation should be encouraged at the institutional level.